HIGHER PREVALENCE OF EXAGGERATED EXERCISE BLOOD PRESSURE IN PEOPLE WITH TYPE 2 DIABETES CAN BE EXPLAINED BY CARDIOVASCULAR RISK FACTORS: THE EXERCISE STRESS TEST COLLABORATION (EXERTION). (April 2021) - Schultz, Martin; Kovacevic, Ann-Marie; Otahal, Petr; Roberts-Thomson, Philip; Stanton, Tony; Wahi, Sudhir; La Gerche, Andre; Hare, James; Selvanayagam, Joseph; Maiorana, Andrew; Venn, Alison; Sharman, James
Abstract : Objective: Exaggerated exercise blood pressure (EEBP) during clinical exercise testing is associated with elevated cardiovascular disease (CVD) risk. Type-2 diabetes (T2DM) is thought to be associated with higher prevalence of EEBP, but this has never been determined in a large clinical population, which was the aim of this study. Design and method: Clinical exercise test records were analysed from 15, 994 people (mean age 53 ± 13 years, 59% male) referred for the Bruce treadmill protocol (stages 1–4 + peak) at 4 Australian public hospitals. Exercise records including blood pressure (BP) were linked to administrative datasets (hospital and emergency admissions) to define clinical characteristics and classify prior history of T2DM (n = 1, 345) vs. no-T2DM (n = 14, 649). EEBP was defined > 90th centile for each exercise stage. Exercise BP was regressed on T2DM history, adjusted to consider CVD risk factors. Results: EEBP prevalence (stage-1: + 4.1%; stage-2: + 4.4%; stage-3: + 4.9%; stage-4: + 4.8%; peak: + 1.9%, P < 0.05 respectively) and exercise systolic BP (stage-1: + 4.25, stage-2: + 4.52, stage-3: + 4.43, stage-4: + 3.08, peak: + 0.75 mmHg, P < 0.05 respectively) were higher across all exercise stages in T2DM vs. no-T2DM. However, all differences were abolished by adjustment for either: age, sex, peak workload, CVD history, or pre-exercise BP. Restricting analyses to those with normal pre-exercise BP (<140/90 or < 130/90 mmHg) revealed no differences in exercise BP or EEBP prevalence between T2DM and no-T2DM. Conclusions: This is the first study to confirm higher prevalence of EEBP in T2DM, but this is explained by accompanying CVD risk factors. Identification of EEBP should prompt aggressive CVD risk factor modification in T2DM.